SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL SERAT KULIT BATANG SAGU (Metroxylon sago ROTTB.) BERDASARKAN UKURAN SERAT - Handayani, Geni Saputri; Dirhamsyah, M; Nurhaida, .; Setyawati, Dina (Universitas Tanjungpura, 2019)
Wood is the most used basic material for daily life, such as material construction, furniture, appliances, and etcetera. This causes the increase of the necessity of wood in the other hand, the availability of wood are decrasing. On of the solutions for this problem is the particle-board from the agriculture waste which is sago. One of the sago parts which can be used is the sago bark. It contains more number of cellulose and lignin then dago dregs and it also contains bigger cellulose and lignin than woods, so it can be used as particle-board. The fibers used are 5 cm, 10 cm, and 15 cm. The citterate solution concentrate is 20% which was mixed with the particle-board. These particle mixtures were in an oven in 24 hours. The production of particle-board with the target of density 0,6 g/cm2 and forged in 1800 C within 15 minutes. The aim of this research is to find out the size of fibers for the particle-board. The best quality of particle board based on JIS 5908 standard is on the 10 cm fiber , with board mechanical characteristicÂ : the flexibility module 22801,8196 kgf/cm2, the fracture module 334,9006 kgf/cm2, and the screw holding strength 46,5448 kgf/cm2. The physical characteristic of water concentrate 10,6249 % and the water absorption 66,8314 %. The score of dense/thickness development and internal bonding did not quality JIS 5908 A (2008). In general, the result of the research showed that longer the size of fibers the better the quality would be produced. Keywords : fiber size, oven duration, particle-board, sago bark